Over the influence: The HIV care continuum among methamphetamine-using men who have sex with men. (1st November 2018) - Jin, Harry; Ogunbajo, Adedotun; Mimiaga, Matthew J.; Duncan, Dustin T.; Boyer, Edward; Chai, Peter; Dilworth, Samantha E.; Carrico, Adam W.
Highlights: Describes the HIV care continuum in methamphetamine-using sexual minority men. Housing and substance use disorder treatment could optimize the HIV care continuum. Underscores the need to integrate HIV care and substance use disorder treatment. Abstract: Background: HIV-positive persons who use stimulants such as methamphetamine experience greater difficulties in navigating the HIV care continuum. In the era of HIV treatment as prevention (TasP), little is known about the prevalence and correlates of success along the HIV care continuum among people who use stimulants. Setting: San Francisco, California USA Methods: Cross-sectional study that enrolled 129 HIV-positive men who have sex with men (MSM) from 2013 through 2017 who had biologically confirmed, recent methamphetamine use. Multivariable logistic regressions were built to identify correlates of success across the HIV care continuum. Results: Although two-thirds (87/129) of participants had undetectable HIV viral load (<40 copies/mL), only one-in-four (32/129) reported taking at least 90% of their antiretroviral therapy (ART). Those who were homeless in the past year (adjusted odds ratio [aOR] = 0.20; 95% CI = 0.06–0.65) had 80% lower odds of being undetectable and adherent to ART. Substance use disorder treatment was associated with 77% lower odds of being engaged in HIV care (aOR = 0.23; 95% CI = 0.06–0.84) but also close to 3-fold greater odds of being adherent to ART (aOR = 2.91; 95% CI = 1.12–7.60). Conclusion: Despite the fact that many HIV-positive, methamphetamine-using MSM are able to achieve undetectable viral load in this sample, difficulties with ART adherence threaten to undermine the clinical and public health benefits of TasP. Expanded efforts to boost the effectiveness of TasP in this population should focus on meeting the unique needs of homeless individuals, optimizing ART adherence, and facilitating the integration of HIV care with substance use disorder treatment.